1994
DOI: 10.1113/jphysiol.1994.sp020088
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glibenclamide on frog skeletal muscle: evidence for K+ATP channel activation during fatigue.

Abstract: 1. The purpose of this study was to determine whether ATP-sensitive K+ (KATP) channels are activated and contribute to the decrease in force during fatigue development in the sartorius muscle of the frog, Rana pipiens. Tetanic force (elicited by field stimulation), action potential and membrane conductance (using conventional microelectrodes), were measured in the presence and absence of glibenclamide, a KATP channel antagonist. Experiments were performed in bicarbonate-buffered solutions at pH 7-2.2. In unfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 40 publications
8
69
2
Order By: Relevance
“…ϩ (K ATP ) channels couple the intermediary metabolism to cellular activity and play important roles in numerous cellular functions such as insulin secretion, neuronal excitability, vascular tones, and muscle contractability (1)(2)(3)(4)(5)(6). The K ATP channels consist of the pore-forming Kir6 and sulfonylurea receptor (SUR) 1 subunits.…”
Section: Atp-sensitive Kmentioning
confidence: 99%
“…ϩ (K ATP ) channels couple the intermediary metabolism to cellular activity and play important roles in numerous cellular functions such as insulin secretion, neuronal excitability, vascular tones, and muscle contractability (1)(2)(3)(4)(5)(6). The K ATP channels consist of the pore-forming Kir6 and sulfonylurea receptor (SUR) 1 subunits.…”
Section: Atp-sensitive Kmentioning
confidence: 99%
“…In the absence of K ATP channel activity, the depolarization can be as high as 50 mV under both conditions. This depolarization has been shown to be sufficiently large enough to activate the Ca 2+ channels in transverse tubules, leading to an uncontrolled Ca 2+ influx, large increases in resting intracellular Ca 2+ and in force (Cifelli et al, 2008;Cifelli et al, 2007;Gong et al, 2000;Light et al, 1994;Matar et al, 2000). As a consequence of the increases in resting [Ca 2+ ], there is greater use of ATP by the Ca 2+ and myosin ATPases, which worsen the possibility of a metabolic catastrophe.…”
Section: Regulation and Impact Of The K Atp Channelmentioning
confidence: 99%
“…at between 10 and 15 mV during repeated muscle contractions (Cifelli et al, 2008;Comtois et al, 1995;Light et al, 1994), whereas it does not change during metabolic inhibition (Gramolini and Renaud, 1997). In the absence of K ATP channel activity, the depolarization can be as high as 50 mV under both conditions.…”
Section: Regulation and Impact Of The K Atp Channelmentioning
confidence: 99%
“…It was demonstrated that ATP inhibits the K ATP channels and that the inhibitory effect of ATP is reduced by lowering of pH (6). It was originally suggested that the channels are activated only in metabolically exhausted muscle fibers (4) and that the activity of the channels contributes to the decrease in force during fatigue in frog muscle (15). However, this hypothesis is not supported by later studies also using frog muscle (20).…”
mentioning
confidence: 99%